Automatic fertigation system in urban farming / Nur Ilylia Najmi Amiruddin - Amiruddin, Nur Ilylia Najmi (2019)
Fertigation system is a well-known system in the agriculture where it is used to distribute water, fertilizer and other water-soluble product into the soil. This project aims to ease urban farming in high volume by introducing an agricultural system that is automated and monitored. The system is divided into 2 separate scopes: Hardware development and software development. The hardware development is talk about the project framework, the flowchart, and circuit framework. While the software development is talk about the codes and the algorithm of the system. The project is done with the objective to reduce water and fertilizer wastage and also to create an automatic system that can ease the farmers.